2020
DOI: 10.1002/ece3.6508
|View full text |Cite
|
Sign up to set email alerts
|

Genetic adaptation of Tibetan poplar (Populus szechuanica var. tibetica) to high altitudes on the Qinghai–Tibetan Plateau

Abstract: Plant adaptation to high altitudes has long been a substantial focus of ecological and evolutionary research. However, the genetic mechanisms underlying such adaptation remain poorly understood. Here, we address this issue by sampling, genotyping, and comparing populations of Tibetan poplar, Populus szechuanica var. tibetica , distributed from low (~2,000 m) to high altitudes (~3,000 m) of Sejila Mountain on the Qinghai–Tibet Plateau. Population structure analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 89 publications
0
0
0
Order By: Relevance
“…Previously, Zheng et al [18] revealed the presence of altitudinal adaptation in the Tibetan poplar population. Two hotspot regions of the genome were detected, one of which (four genes, chromosome 15) was associated with altitudinal variation, and the other (10 genes, chromosome 6) with response to solar radiation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, Zheng et al [18] revealed the presence of altitudinal adaptation in the Tibetan poplar population. Two hotspot regions of the genome were detected, one of which (four genes, chromosome 15) was associated with altitudinal variation, and the other (10 genes, chromosome 6) with response to solar radiation.…”
Section: Discussionmentioning
confidence: 97%
“…De Kort et al [17] studied regional climate adaptation of drought-sensitive black alder (Alnus glutinosa L.) across Europe and reported significant associations between variation of several loci of this tree species and temperature and latitude. Zheng et al [18] discovered two specific regions in the Tibetan poplar (Populus szechuanica var. tibetica) genome associated with altitude and response to the solar radiation level, and gained insight into the genetic mechanisms underlying the adaptation to highlands in plants.…”
Section: Introductionmentioning
confidence: 99%